The Impact of Masculinity Beliefs and Political Ideologies on Men’s Backlash Against Non-Traditional Men: The Moderating Role of Perceived Men’s Feminization - Vincenzo Iacoviello (Ubiquity Press, 2021)
Traditional masculinity norms are still prevalent in our societies. As a result, men who deviate from these norms face adverse reactions (i.e., backlash), mainly from other men. The present research investigated whether the perceived threat to gender status quo accounts for this phenomenon. In two studies using a sample of heterosexual men ('Ntotal' = 338), we measured male participants’ endorsement of traditional masculinity beliefs and their political orientation. As a means of examining the role of threat to the gender status quo, we then manipulated whether traditional masculinity norms remained stable (stability) or changed across time (men’s feminization). Finally, we assessed participants’ evaluation of men who deviate from traditional masculinity norms (i.e., a backlash against a non-traditional man). This target was either compared to a traditional man (Study 1) or a traditional woman (Study 2). The general hypothesis was that men who are strongly motivated to maintain the gender status quo (i.e., those who endorse traditional masculinity beliefs to a higher extent or support right-wing political ideologies) should show greater backlash, particularly when the gender status quo is threatened (i.e., in the men’s feminization condition). The results of a small-scale meta-analysis supported our hypothesis. We discuss the impact of these findings on the gender literature.